Antibiogram of bacteria isolated from automated teller machines in Hamadan, West Iran - Mahmoudi, Hassan; Arabestani, Mohammad Reza; Alikhani, Mohammad Yousef; Sedighi, Iraj; Kohan, Hamed Farhadi; Molavi, Mohammad (German Medical Science GMS Publishing House, 2017)
Aim: Bacteria are ubiquitous in the environment. In keeping with the continued expansion of urbanization and the growing population, an increasing number of people use automated banking, i.e. automated teller machines (ATMs). The aim of this study was to investigate the bacterial contamination and its antibiotic sensitivity on computer keyboards located at ATMs in Hamadan province, Iran. Method: Out of 360 ATMs at four locations in Hamadan, 96 were randomly selected for this study. The antibiotic susceptibility pattern of all isolates was determined by the agar disk diffusion method using gentamicin (10 µg), vancomycin (30 µg), trimethoprim/sulfamethoxazole (25 µg), amikacin (30 µg), tobramycin (10 µg), cephalotin (30 µg), norfloxacin (5 µg), and ceftizoxim (30 µg) disks. Results: Melli and Saderat Banks had the most frequently contaminated ATMS, with 18 (27.7%) and 12 (18.5%), respectively. The most frequently isolated bacteria were in 12 (18.5%) ATMs, in in 11 (16.9%), in 6 (9.2%), spp. in 8 (12.3%), spp. in 2 (3.1%), in 6 (9.2%), in 3 (4.6%), and spp. in 5 (7.69%) cases. All isolated bacteria were susceptible to gentamicin, cephalotin, tobramycin, amikacin, norfloxacin, and vancomycin. The resistance rate to trimethoprim/sulfamole was 50%. Conclusion: All tested ATM keyboards were contaminated with at least one species of bacteria. Based on these findings, it is recommendable to disinfect the hands after entering one's own apartment, work area or a hospital, in order to hinder the spread of critical pathogens in the personal environment or in the hospital.